Microstructure and mechanical properties of micro-nano Ti2AlC-reinforced TiAl composites. (July 2022) - Ma, Tengfei; Li, Qiaoyu; Wang, Yupeng; Wang, Xiaohong; Dong, Duo; Zhu, Dongdong
Abstract: In order to improve the mechanical properties of TiAl alloys, micro-nano Ti2 AlC-reinforced TiAl composites were successfully fabricated by means of spark plasma sintering (SPS) using the ball-milled multilayer graphene oxide and Ti–48Al–2Nb–2Cr pre-alloyed powders. The micro-nano Ti2 AlC phase precipitated at the interface between α2 -Ti3 Al and γ-TiAl phases utilizing the reaction of TiAl and high-activity graphene. Fully lamellar structure was obtained after sintering above 1300 °C, and Ti2 AlC phase characteristic were depended on sintering temperature and graphene content. The compressive strength and fracture strain of TiAl-0.5G alloy were improved at room temperature and elevated temperature, which was improved by 23.61% and 5.03% compared to the TiAl-0G alloy at room temperature. The tribological properties of TiAl composites were significantly improved by micro-nano Ti2 AlC at the room temperature, and the average friction coefficient of TiAl-0.5G alloy is 0.217 compared with TiAl-0G alloy is 0.312, and the wear mechanism is ploughing wear. The micro-nano Ti2 AlC improves the strength and oxidation resistance of TiAl composites at 650 °C, which is detrimental to the wear resistance due to the lower ductility and the third wear by the loose oxide particles at elevated temperature. Highlights: Micro-nano Ti2 AlC-reinforced TiAl alloys was fabricated via SPS. The compressive strength and plasticity were improved simultaneously by micro-nano Ti2 AlC phase. The room-temperature tribological property was significantly improved by Ti2 AlC.